1998
DOI: 10.1074/jbc.273.32.19993
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin-dependent Protein Kinase IV Is Cleaved by Caspase-3 and Calpain in SH-SY5Y Human Neuroblastoma Cells Undergoing Apoptosis

Abstract: We have previously demonstrated cleavage of ␣-spectrin by caspase-3 and calpain during apoptosis in SH-SY5Y neuroblastoma cells (Nath, R., Raser, K. J., Stafford, D., Hajimohammadreza, I., Posner, A., Allen, H., Talanian, R. V., Yuen, P., Gilbertsen, R. B., and Wang, K. K. (1996) Biochem. J. 319, 683-690). We demonstrate here that calcium/calmodulin-dependent protein kinase IV (CaMK IV) is cleaved during apoptosis by caspase-3 and calpain. We challenged SH-SY5Y cells with the proapoptotic agent thapsigargin. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 70 publications
3
57
1
Order By: Relevance
“…CaMK IV but not CaMK IIb is rapidly cleaved during cell death with kinetics that precede the observed decrease in CaMK activity. 74 In addition to CaMK IV, CaMK IIa and the upstream activator CaMK kinase (CaMKK) are also cleaved in vivo in SH-SY5Y cells exposed to staurosporine, a finding that is reminiscent of the observed sequential cleavage of several MAPK components such as MEKK-1 and MSTs. CaMK IV is also cleaved by calpain to a 40 kD fragment in a manner that is inhibited by a calpain inhibitor, both in vivo and in vitro.…”
Section: (Viii) Signaling Molecules With Pleiotropic Functionsmentioning
confidence: 92%
See 2 more Smart Citations
“…CaMK IV but not CaMK IIb is rapidly cleaved during cell death with kinetics that precede the observed decrease in CaMK activity. 74 In addition to CaMK IV, CaMK IIa and the upstream activator CaMK kinase (CaMKK) are also cleaved in vivo in SH-SY5Y cells exposed to staurosporine, a finding that is reminiscent of the observed sequential cleavage of several MAPK components such as MEKK-1 and MSTs. CaMK IV is also cleaved by calpain to a 40 kD fragment in a manner that is inhibited by a calpain inhibitor, both in vivo and in vitro.…”
Section: (Viii) Signaling Molecules With Pleiotropic Functionsmentioning
confidence: 92%
“…5 CaMK IV is a serine-threonine kinase with restricted tissue distribution and a high degree of homology to CaMK II. 74 CaMK IV has been implicated in activation of a number of important transcription factors (Table 2). Like the situation for other kinases such as DNA-PK and PKCz, inhibition of CaMK kinase activity is associated with apoptosis.…”
Section: (Viii) Signaling Molecules With Pleiotropic Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two major calpain family proteins, µ-calpain and m-calpain, share a 30 kDa regulatory subunit and require different Ca 2+ concentrations for activation in vitro. Activated calpain acts on a host of endogenous proteins, which include cytoskeletal proteins (fodrin, vimentin, keratin, and tau), PARP, calmodulin-dependent protein kinase IV (CaMKIV), clathrin assembly protein, bax, and even procaspase-3 (Ando et al, 1988;Litersky and Johnson, 1995;McGinnis et al, 1998;Prasad et al, 1998;McGinnis et al, 1999a;Kim and Kim, 2001). Particularly, in many neurodegenerative disorders such as Alzheimer's disease, this calpain systems are involved (Patrick et al, 1999;Lee et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Calpains can also inactivate caspases by cleavage of the pro-caspase form to proteolytically inactive fragments (52,79). In addition, calpain activation in apoptosis can occur concurrently with, or in the absence of, caspase activation (80)(81)(82)(83)(84)(85)(86). In studies described above, we demonstrated that calpains were activated in human breast cancer cells during ß -lap-mediated apoptosis, while caspase activation was not apparent (Fig.…”
Section: Calpain-mediated Apoptosis After ß-Lap-exposure Of Nqol -Expmentioning
confidence: 84%